Evaluation of hypoglycemic potential of Cuminum cyminum and its role in modulation of cognitive function in rats with induced diabetes - Abhishek Kumar; Amit Shekhar; Mitali Dua; Indu Jangra; Umesh Suranagi; Ekta Arora (Journal of Applied Pharmaceutical Research)
Background: This study investigated the effects of Cuminum cyminum (C. cyminum) on cognitive behaviour and acetylcholinesterase (AChE) levels in diabetic rats, comparing its efficacy with Glibenclamide, Sulbutiamine, and Resveratrol.